Thiol redox transitions in cell signaling. - Cadenas, Enrique; Packer, Lester (Methods in enzymology, 2010)
This volume, along with its companion (volume 475), presents methods and protocols dealing with thiol oxidation-reduction reactions and their implications as they relate to cell signaling. The critically acclaimed laboratory standard for forty years, Methods in Enzymology is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. Over 450 volumes have been published to date, and much of the material is relevant even today--truly an essential publication for researchers in all fields of life sciences. *Along with companion volume, provides a full overview of techniques necessary to the study of thiol redox in relation to cell signaling * Gathers tried and tested techniques from global labs, offering both new and tried-and-true methods * Relevant background and reference information given for procedures can be used as a guide to developing protocols in a number of disciplines.